A highly stretchable and deformation-insensitive bionic electronic exteroceptive neural sensor for human-machine interfaces. (February 2021) - Liao, Xinqin; Wang, Wensong; Wang, Liang; Jin, Haoran; Shu, Lin; Xu, Xiangmin; Zheng, Yuanjin
Abstract: Bionic integrated sensing devices with numerous distributed electronic elements substantially expand the human's interactive control capabilities. Several difficulties need to be overcome, including intricate interconnections, complicated structures, and electromagnetic interference/compatibility in signal transmission. In addition, retention of device's functionalities under high deformation is desired, while it faces huge challenges to achieve stretchability and deformation insensitivity. Herein, a highly stretchable and deformation-insensitive bionic electronic exteroceptive neural sensor is first presented and fabricated from the functional composite of polyester thread coated with carbon nanotubes. The bionic electronic exteroceptive neural sensor features all-in-one bionic multifunctional characteristics, which effectively avoids the use of numerous distributed electronic elements. Importantly, it achieves high stretchability and characterizes unprecedented deformation-insensitive functional property. The properties enable the bionic electronic exteroceptive neural sensor to serve as a wearable device and function continuously without interference even when being greatly stretched (100% strain). Other prominent advantages of the bionic electronic exteroceptive neural sensor are excellent stability (> 15, 000 cyclical tests), rapid response (≤ 15 ms), high robustness, geometrically hierarchical sensing, and personalized cuttability. The tremendous potential applications of the bionic electronic exteroceptive neural sensor are demonstrated in the fields of human-machine interactions, information security system, and Internet of things. Graphical Abstract: ga1 Highlights: A stretchable and multifunctional all-in-one electronic exteroceptive sensor is demonstrated by using carbon nanotubes@polyester thread. The stretching insensitivity of the electronic exteroceptive sensor is first achieved, which enables device to operate efficiently and steadily even when being largely deformed (100% strain). The stretchable bionic synaptic plasticity of the electronic exteroceptive sensor is first demonstrated, revealing the device's enormous potential for sophisticated human-machine interactions and neuroprosthetics. Ultra-robustness to different mechanical stimulations, cuttability, and excellent durability against > 15, 000 repetitive stimulations are the important stable characteristics of the electronic exteroceptive sensor Geometrically hierarchical sensing, spatiotemporal resolution function, and rapid response (≤ 15 ms) endow the great potential of the electronic exteroceptive sensor for multifunctional touch interactions